Investigating and Determining the Priorities for Capital Organizing in Iran - Mohammad Mirehei; Amir Fathi; Sohrab Amirian; Hatem Parnian (جغرافیا و پایداری محیط)
1- Introduction Reconstruction and industrial development policies in the last century in Iran has caused over- centralization of population and public services. Rapid and uncontrolled increase in the population of Tehran in the last few decades leads to both increasing the densities and pollution, and decreasing the quality of services and available resources. All these policies have increased migration from border regions to Tehran, which can threaten the security of the country. Various methods have been examined to organize Tehran, but none of them could control the increase of population or decrease the pressure on infrastructures and resources in long term. The problems created by poor planning in different levels in Tehran not only are just the issues of this province but also affect all other provinces. In the last two centuries, Tehran has been transformed to the center of country’s infrastructures and specially the network of ways. The network of all highways, railways and airways in Iran is so structured, that Tehran is practically the center all of them. Tehran is also the source of many problems in other fields like economic, political, cultural, social and environmental sects. The subject of organizing the capital affects not only this city and its surrounding regions but also whole the country directly or indirectly. So to solve Tehran’s problems we should consider the different aspects of spatial planning in Tehran and whole country. Region of this study:Tehran is the capital of Islamic Republic of Iran, which is located in the south of Alborz Mountains; one of the central provinces of Iran. In 2006, ratio of the population of Tehran agglomeration ratio to the population of country was 18.13. In 2006, 52% of investment (governmental and private), was concentrated in Tehran. 2-Materials and Methods In this investigation statistical society consists of spatial planning specialists, and related organizations and institutions. This investigation is going to prioritize the method of organizing the Capital by spatial planning approach, using the technic of AHP, based on certified survey whose essence is qualitative and quantitative and its purpose is developmental. The method of gathering information in this investigation are librarian and field (questioner) in which the data and statistics were gathered from essays, books and related sources and also interviews with experts . In the next step, we prepared a questionnaire whose target society was elite. For scoring we used nine degree scale of L. Saaty. Then, the mean of all criteria and choices of questionnaires extracted and inserted in expert choice software. 3- Results and Discussion In this research, following criteria have been chosen to investigate and determine the priorities for organizing the Capital with spatial planning approach: implementation capability, implementation speed, dimensions of influence, environmental, political, and economic and security considerations and low implementation costs. Studying the evidence, different documents and interview with elite and experts, we obtained many choices categorizing them into five main groups or choices, like internal organization of Tehran city, decentralization, make and strengthening opposing poles, spatial approach and displacement of the Capital city. Then the choices were prioritized on the basis of specialist’s viewpoints and by considering the effect of each criterion. 4-Conclusion Implementation capability in the organizing Capital is known as the best criterion. Displacement of the capital city has last option priority and the importance of practicing has been estimated 5%. In the result of organizing and decentralization Capital city conference at 2015, this issue was referred to. However, almost all domestic and foreign pundits participating in the conference disagreed to displacing Tehran like a capital city. The opinions of these scientists are based on the organization and decentralization. Because finding a suitable geographical area in the country to displaced Capita city there is not a simple task, displacing the Capital city requires a lot of financial credit. But there are many ways to organize the capital appearing in the form of five main options in the preset study. So, it can be concluded that, the best way to organize the capital not only is not a particular option, but needs to examine some options and still other options must be considered. As we noted in the materials and methods section, this option should mostly pay attention to internal organization of the Tehran city and in next priorities should focus on decentralization of the capital, territorial approach and make and strengthening opposing poles for Tehran. According to Tehran today, and by using the result of this research and experience of other countries in dealing with Capital problems, some steps are provided to organize Tehran: